The Politics of Female Alliance in Early Modern England - O'Leary, Niamh J., 1980-; Luckyj, Christina, 1956- (Book collections on Project MUSE., 2017)
The Politics of Female Alliance in Early Modern England expands our knowledge of yet another facet of female alliance: the political. Archival discoveries as well as new work on politics and law help shape this work as a timely reevaluation of the nature and extent of women's political alliances.